Abstracts 2014
DOI: 10.1136/bjsports-2014-094114.109
|View full text |Cite
|
Sign up to set email alerts
|

110 Is Type 1 Diabetes Mellitus Associated With Lower Limb Tendon Pathology? A Systematic Review

Abstract: Introduction Type 1 diabetes mellitus (T1DM) occurs when insulin-producing cells are destroyed by an autoimmune response, resulting in hyperglycaemia. Hyperglycaemia accelerates collagen cross-linking in tendons, which can deteriorate tendon structure and predispose to tendon injury (Reddy 2003). Tendon pathology has been observed in the type 2 DM (T2DM) population (Akturk et al. 2007; Papanas et al. 2009), however little is known about T1DM and tendon pathology. This review examines whether there is an associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The prevalence of T1DM among individuals with Achilles tendinopathy – based on GP diagnosis codes in electronic records – is 1.8 % (95 % confidence interval = 0 to 4.5) and therefore not significantly different from the point estimate for the Dutch population (0.8 %) [ 17 ]. Results of the systematic review found there was a complete absence of data on tendon structure in people with T1DM [ 18 ]. Understanding tendon integrity and response to load in the T1DM population is important, as physical activity is a key component of long-term metabolic control of T1DM [ 19 ] and musculoskeletal injury frequently prevents physical activity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of T1DM among individuals with Achilles tendinopathy – based on GP diagnosis codes in electronic records – is 1.8 % (95 % confidence interval = 0 to 4.5) and therefore not significantly different from the point estimate for the Dutch population (0.8 %) [ 17 ]. Results of the systematic review found there was a complete absence of data on tendon structure in people with T1DM [ 18 ]. Understanding tendon integrity and response to load in the T1DM population is important, as physical activity is a key component of long-term metabolic control of T1DM [ 19 ] and musculoskeletal injury frequently prevents physical activity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycaemia accelerates collagen cross-linking in tendons, which can deteriorate tendon structure and predispose to tendon injury (Reddy 2003). Tendon pathology has been observed in the type 2 DM (T2DM) population (Akturk et al 2007;Papanas et al 2009), however little is known about T1DM and tendon pathology. This review examines whether there is an association between T1DM and lower limb tendon pathology.…”
mentioning
confidence: 99%